Varieties of Religious (Non)Affiliation: A Primer for Mental Health Practitioners on the "Spiritual but Not Religious" and the "Nones". Issue 5 (May 2020) - Saunders, David; Norko, Michael; Fallon, Brian; Phillips, James; Nields, Jenifer; Majeed, Salman; Merlino, Joseph; El-Gabalawi, Fayez
Abstract : Abstract: Given changing demographics of religiosity and spirituality, this article aims to help clinicians understand contemporary trends in patient religious and spiritual orientation. It first identifies and describes the evolving varieties of religio-spiritual orientation and affiliation, as identified in survey studies. Particular attention is given to the examination of those who identify as spiritual but not religious (SBNR) and None ( i.e., no religious affiliation), which is important to mental health practice because many patients now identify as SBNR or None. Next, empirical data are considered, including what the literature reveals regarding mental health outcomes and SBNRs and Nones. We conclude with a summary of the main points and five recommendations that mental health practitioners and researchers need to consider regarding this increasingly large portion of the population.